Experimental Research on Performance of New Gas Drainage Borehole Sealing Material with High Fluidity. (9th February 2021) - Guo, Xin; Xue, Sheng; Zheng, Chunshan; Li, Yaobin
Abstract : To ensure the sealing effect of gas extraction borehole in underground coal mine and improve the concentration of gas extraction, a kind of high-flow sealing material which can be injected into the microcracks around borehole was developed. The ultrafine cement as the base material, with water-reducing agent, expansion agent, retarder, the material, and water combined stir, will form a kind of colloid with high fluidity and slightly expansibility. This paper analyzes the differences between the new high-fluidity sealing material and ordinary cement materials in expansion performance, compressive strength, and sealing performance. Scanning electron microscope and mercury intrusion method were used to analyze the differences in microscopic morphology and pore structure of these two materials. The experimental results show that the new high-fluidity sealing material has an excellent fluidity of 295.5 mm with an expansion rate of 60 d being 1.562%. The new high-fluidity sealing material is convenient for grouting with strong material permeability and superior sealing performance. Field test results show that the effect of the new high-fluidity sealing material is better than the ordinary cement materials. The average drainage concentration and flux during the drainage period were 59.07% and 0.243 m 3 /min, respectively, which showed that the drainage efficiency was significantly improved. This novel sealing material is of great significance for improving the efficiency of drilling and drainage.